Relationship Between Occupational Cognitive Failures and Personality Traits in Iranian Nurses Working in Emergency Departments - Parisa Bozorgzad; Ghazaleh Salighehdar; Hamid Peyrovi; Hanieh Gholamnejad; Maryam Mahmoudi; Shima Haghani; Mehdi Manoochehri (نشریه پرستاری ایران)
Background & Aims Emergency department (ED) nurses are exposed to cognitive failures, which refers to impaired perception, memory and motor function. Their personality traits seem to have a role in the occurrence of these failures. This study aims to determine the relationship between cognitive failure and personality traits of ED nurses in Urmia, Iran. Materials & Methods This descriptive-correlational study was conducted on 165 nurses working in the EDs of hospitals affiliated to Urmia University of Medical Sciences from February to May 2021. Data were collected using the cognitive failure questionnaire (CFQ) and the NEO five-factor personality inventory. Descriptive statistics (frequency, percentage, mean, and standard deviation) were used to describe variables. Data were analyzed with one-way analysis of variance, independent t-test, Pearson correlation test, and multiple regression analysis in SPSS software, version 22. The significant level was set at 0.05 Results The mean total score of CFQ was 1.56±0.78. Regarding the dimensions of CFQ, the highest mean score was for the distractibility dimension (1.66±0.77), while the lowest mean score was for the dimension of false triggering (1.42±0.93). Regarding personality traits, the highest mean score was for conscientiousness (29.98±6.74), while the lowest mean score was for neuroticism (21.21±6.56). We found a significant and negative correlation between cognitive failure (and its dimensions) and all personality traits (P<0.001). Furthermore, we identified a significant relationship between nurses’ cognitive failures and the use of sedatives (P=0.001), work shift (P<0.001), and satisfaction with salary (P=0.041). Conclusion The cognitive failure level of ED nurses in Urmia is moderate. There is a significant relationship between their cognitive failure and personality traits. The nurses with high conscientiousness have fewer occupational cognitive failures. In contrast, those with high neuroticism have more occupational cognitive failures.